Impact of AgNP on the Inhibition of Fecal Coliforms by 3DP-Modified Chitosan Membranes - Anthony C. Ogazi; Peter O. Osifo (Chemistry Proceedings, 2024)
This study investigated the role of silver nanoparticles (AgNP) in the inhibition of fecal coliforms by 3D-printed modified chitosan filtration membranes. The composite membranes demonstrated steady improvement in antibacterial activity against the bacteria. The amount of silver ions (Ag+) added to chitosan/AgNP filtration membranes affectshow well they kill microbes. An increase in the concentration of AgNP improved the chitosan matrix’s antibacterial activity and effectively reduced fecal coliforms. However, only fecal microorganisms in contact with Ag+ experienced complete destruction or inhibition from the modified composite membranes. The membrane surface structural layer revealed that the CS/AgNP composite consisted of carbon (C), oxygen (O), silver (Ag), and small amounts of sulfur (S). When active fecal bacteria cells came into contact with the CS/AgNP membrane structure, it was able to break down their barrier properties. The positively charged sites of the modified chitosan matrix effectively interacted with negatively charged microbial cells and eventually reduced fecal activities by 99.9%. The measured Ag concentrations in the effluent decreased over a period of time, suggesting that an increase in the volume of effluent would bring about a reduction in the concentration of Ag ions. Therefore, optimizing the amount of Ag nanoparticles in the modified chitosan composite is necessary to achieve the most favorable membrane separation performance for treating polluted surface water.